2002
DOI: 10.1002/cae.10026
|View full text |Cite
|
Sign up to set email alerts
|

Low cost vision system for an educational platform in artificial intelligence and robotics

Abstract: This paper presents a web-cam based vision system for performing image processing in real time. It was implemented as part of an AI and Robotics educational platform designed to study collaborative moving robots in a dynamic environment. A color based image segmentation algorithm was developed with careful attention to algorithm efficiency, due to hardware limitations for the maximum frame rate. This led to a simple and cost-effective vision system that is able to detect and identify several mobile robots thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Different educational low cost resources have emerged with the intention of facilitate the teaching‐learning processes, generally aimed at learning the programming of electronic devices, the assembly and welding of electronic devices and the mounting of mechanical components. A low‐cost vision system was developed for the teaching of artificial intelligence and robotics . It was expected that students can present their own solutions based on the physical response of sensors and actuators to different situations and scenarios; in this case applied to the manufacturing of soccer robots.…”
Section: Related Workmentioning
confidence: 99%
“…Different educational low cost resources have emerged with the intention of facilitate the teaching‐learning processes, generally aimed at learning the programming of electronic devices, the assembly and welding of electronic devices and the mounting of mechanical components. A low‐cost vision system was developed for the teaching of artificial intelligence and robotics . It was expected that students can present their own solutions based on the physical response of sensors and actuators to different situations and scenarios; in this case applied to the manufacturing of soccer robots.…”
Section: Related Workmentioning
confidence: 99%
“…Studies suggest that there are many learning tools involving the use of robots in computer instruction; these studies show significant achievements by analyzing questionnaires and follow‐up surveys of students . In addition, it has been found that a goal, such as a prize competition, can effectively motivate students .…”
Section: Use Of a Robot In The Classmentioning
confidence: 99%
“…The author has successfully tested the use of simulation software in combination with experimental setups in other educational applications such as in robot soccer [2].…”
Section: Introductionmentioning
confidence: 99%